Flipped classroom in EFL: a teaching experience with pre-service teachers - Birova, Lenka; Ruiz-Cecilia, Raúl; Guijarro-Ojeda, Juan Ramón (Frontiers in Psychology, 2023)
This research aims to test a flipped classroom model to improve students' English proficiency. To achieve this goal, two research questions were posed: RQ1 "Does the suggested model of flipped classroom teaching strategy increase the learners' accuracy in the use of grammar in the target language more than the non-flipped active-learning strategy used?" and RQ2 "Does the suggested model of Flipped Classroom teaching strategy increase learners' listening skills in the target language more than the non-flipped active-learning strategy used?" The participants involved in the study were 55 students from the Faculty of Education, University of Trnava (Slovakia), comprising 45 females and 10 males. All participants were pre-service teachers of English language and literature in their first year of undergraduate studies. The research had a semi-experimental pretest/post-test design which was given to the control and the experimental group. The results show that students in the flipped classroom had a statistically significant positive effect on the participants' listening skills. As for grammar, both the control and the research group improved, but the results were not statistically significant. These findings partially match former studies, where language accuracy was also an indicator of flipped classroom success. The implications of this research are high since listening, often referred to as the "Cinderella" of language skills, has frequently been overlooked in EFL classes, leading to students not reaching expected proficiency levels.